The Problematic Duhamel Pouch in Hirschsprung’s Disease: Manifestations and Treatment - Chatoorgoon, K.; Pena, A.; Lawal, T. A.; Levitt, M. (European Journal of Pediatric Surgery, 2011)
The Duhamel operation is commonly employed to treat Hirschsprung’s disease (HD). We have seen a number of patients referred to our center with problems following a Duhamel procedure performed elsewhere, and have analyzed our experience with these children.We reviewed 17 patients with Hirschsprung’s disease who underwent a Duhamel procedure elsewhere, in whom we performed a redo pull-through for persistent symptoms of constipation, impaction, and enterocolits.All patients (n=17) had constipation/impaction or enterocolits, 9 of whom were soiling due to overflow incontinence. Biopsies of the pulled-through bowel found 6 patients with persistent aganglionic bowel and 2 patients with ganglion cells present but hypertrophic nerves, a finding we interpreted as “transition zone bowel”. The remaining 9 patients without a pathological indication for reoperation had a mega Duhamel pouch. All patients underwent a redo operation: 8 via a posterior sagittal approach (7 with a laparotomy, 1 without) and 9 by a transanal, Swenson-type resection with a laparotomy. The posterior sagittal approach was used in cases with severe pelvic fibrosis considered unsuitable for a transanal operation. 15 patients were followed up postoperatively for longer than 2 months, 13 of whom now have voluntary bowel movements, including 8 who need a small dose of laxatives. 2 patients are still diverted.Although perhaps successful for many patients around the world, the Duhamel pull-through can leave patients with significant symptoms, including impaction and overflow incontinence. It is unclear why some patients with a Duhamel pouch do not empty well. Clearly, those patients with a mega Duhamel pouch suffer from impaction. These patients need to be detected, because reoperation with resection of the Duhamel pouch can dramatically improve their quality of life.
Keywords: Hirschsprung’s disease; Duhamel procedure; reoperation; constipation; megarectum